Approaches, foundations, issues, and models of interfaith relations - Singh, David Emmanuel; Schick, Robert, 1957-; I.S.P.C.K. (Organization); Henry Martyn Institute of Islamic Studies (Delhi : Jointly published by Indian Society for Promoting Christian Knowledge and Henry Martin Institute of Islamic Studies, Hyderabad, 2001)
Articles previously published in Journal of the Henry Martyn Institute; chiefly on Muslim-Christian relations.
Models of Interfaith Relations An example of inter-religious respect: the Inner City Parish Church of Pecs, Hungary/ Cees Bouma-- Islam and Inter-Religious Encounter in Trinidad-- Called to be Messengers of Reconciliation: our role in a multireligious society/ Poulose Mar Poulose-- Reflections on a pastoral ministry in a pluralistic society/ Ernest W.. Talibuddin-- Islam and Christianity as sources of conflict and resources for peace on the Island of Mindanao in the Philippines: a case study of two interfaith peace-building initiatives/ David Dyck
Includes bibliographical references.
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam